The effect of a rehabilitation program to develop some physical characteristics for partial meniscus tear for soccer players aged 20-24 years - Ahmed kamil (College of Physical Education and Sport Sciences, 2023)
This research aims to identify the extent of the effect of a rehabilitation and physical program on meniscus resection for football players. The researcher used the experimental method with one experimental group for pre- and post-measurement, and the sample number was 7 patients Of football players whose ages ranged from (18 to 24 years), the researcher used the front muscle strength test, standing on one leg, the back muscle strength test, the Balsom agility test, and the balance test. The physical program lasted 10 weeks. The rehabilitation program contained 30 strength training units in the Iron Hall, which included three units per week. The unit time was 50-60 minutes. The program also contained two rehabilitation units in the aquatic environment, with a total of 20 rehabilitation units. The program also contained exercises The balance was 30 rehabilitation units. The researcher used the statistical method SPSS The most important conclusions were the presence of a significant statistical significance between the results of the pre- and post-tests, in favor of the post-tests. The researcher recommends conducting future studies on the criteria for returning to competition, and to be guided by the program Physical and scientific tests used in research that played a role in moving from one training stage to another.